2013
DOI: 10.1186/1471-2334-13-516
|View full text |Cite
|
Sign up to set email alerts
|

The value of radiographic findings for the progression of pandemic 2009 influenza A/H1N1 virus infection

Abstract: BackgroundMost illnesses caused by pandemic influenza A (H1N1) pdm09 virus (A/H1N1) infection are acute and self-limiting among children. However, in some children, disease progression is rapid and may require hospitalization and transfer to a pediatric intensive care unit (PICU). We investigated factors associated with rapid disease progression among children admitted to hospital for A/H1N1 infection, particularly findings on initial chest radiographs.MethodsIn this retrospective study, we investigated the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Studies that have analyzed only patients with severe H1N1 admitted to an ICU have also demonstrated that symptoms were similar to typical seasonal H1N1, such as cough, dyspnea, fever, myalgia and headache [1]. The results are also comparable to studies that have analyzed mild and severe infections [7].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Studies that have analyzed only patients with severe H1N1 admitted to an ICU have also demonstrated that symptoms were similar to typical seasonal H1N1, such as cough, dyspnea, fever, myalgia and headache [1]. The results are also comparable to studies that have analyzed mild and severe infections [7].…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies have demonstrated that all patients with H1N1 admitted to an intensive care unit had at least an abnormal conventional radiograph (CR) at diagnosis. However, there is a relative lack of studies in the literature that have evaluated predictive tools in the evaluation of patients with H1N1 [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia represented one of the most common complications among patients with seasonal influenza, as confirmed in our study. [16,17]. According to the WHO repots, during pandemics and epidemics, the largest number of cases of mortality among seasonal influenza are as a result of secondary bacterial infection presented as pneumonia.…”
Section: Discussionmentioning
confidence: 99%